2015
DOI: 10.1021/acs.jafc.5b04347
|View full text |Cite
|
Sign up to set email alerts
|

Whole Egg Consumption Prevents Diminished Serum 25-Hydroxycholecalciferol Concentrations in Type 2 Diabetic Rats

Abstract: Type 2 diabetes (T2D) is characterized by vitamin D deficiency owing to increased urinary loss of 25-hydroxycholecalciferol (25D). Whole eggs are a rich source of vitamin D, particularly 25D, the circulating form that reflects status. Zucker diabetic (type 2) fatty (ZDF) rats and their lean counterparts were fed casein- or whole egg-based diets for 8 weeks. Whole egg consumption attenuated both hyperglycemia and hypertriglyceridemia, as well as reduced weight gain in ZDF rats compared to casein-fed diabetic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Egg consumption has also been shown to promote weight loss in a limited number of human studies (57, 58). In contrast to our previous findings (20, 21), we did not observe a reduction in body weight gain in ZDF rats fed a whole egg–based diet. Moreover, relative adipose tissue weight not differ between ZDF rats, regardless of dietary treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Egg consumption has also been shown to promote weight loss in a limited number of human studies (57, 58). In contrast to our previous findings (20, 21), we did not observe a reduction in body weight gain in ZDF rats fed a whole egg–based diet. Moreover, relative adipose tissue weight not differ between ZDF rats, regardless of dietary treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…It is widely recognized that obesity is a major risk factor for insulin resistance, which precedes the onset of overt diabetes (1–3). We previously reported that a whole egg–based diet attenuates cumulative body weight gain in the Zucker diabetic fatty (ZDF) rat, a well-characterized genetic model of obesity and T2D (20, 21). The observed attenuation in body weight gain was attributed, in part, to an 8% reduction in body fat in ZDF rats consuming a whole egg–based diet (20).…”
Section: Introductionmentioning
confidence: 99%
“…Specific egg components, such as hen egg lysozymes, have been previously studied in altering gene expression in pig intestinal tissues ( 28 ), but very little information is known about how dietary WE affects endogenous gene expression across specific tissues. The beneficial role of a WE-based diet in maintaining vitamin D status and modulating adverse phenotypic outcomes in both a type 1 diabetes (T1D) and type 2 diabetes (T2D) animal models has been consistently demonstrated ( 12 , 29 ); however, we have not investigated how WE consumption modulates gene expression in a standard rodent model. RNA-sequencing is a powerful tool that can elucidate the influence of dietary patterns at the level of the transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo study addressing the effect of whole egg consumption on T2D is very limited. In Zucker diabetic fatty rats, eight-week feeding of dried whole egg-based diet was shown to reduce blood glucose and triglyceride concentrations, decrease the percentage of body fat, suppress weight gain, and increase circulating 25-hydroxycholecalciferol level, compared to diabetic rats fed with casein-based diet [9,10].…”
Section: Egg Consumption and The Risk Of T2dmentioning
confidence: 99%